A TRANSPOSIÇÃO DOS GAMES PARA O CINEMA: A REPRESENTAÇÃO DAS VIOLÊNCIAS NA ADAPTAÇÃO DE ASSASSIN’S CREED - ISABELA DOMINGUES ALLAMAN (2021)
The present research has as objects of analysis two works: the electronic game Assassin's Creed (2007) and its homonymous film adaptation of 2016, directed by Justin Kurzel, with the objective of analyzing how the representation of violence and its adjacent themes is presented and explored within the narrative context of each of the media. Based on the premise that media products are cultural products that carry production logics and specific languages, producing discourses in their narratives, we intend to a) present the contemporary context of audiovisual and digital media production; b) reflect on violence from a philosophical point of view, highlighting its forms, meanings and social representations; and c) analyze and interpret the representation of the violence made in the two works. Therefore, this study is divided into 3 chapters, the first with a theoretical framework addresses issues related to the media, media and contemporaneity, the second is focused on philosophical issues related to violence and the last analyzes the discourse of objects from an interpretation the philosophical and literary basis of the Assassin's Creed theme.